Galaxy Model Subtraction with a Convolutional Denoising Autoencoder - Liu, Rongrong; Peng, Eric W.; Wang, Kaixiang; Ferrarese, Laura; Côté, Patrick (The Astrophysical journal, 2025)
Galaxy model subtraction removes the smooth light of nearby galaxies so that fainter sources (e.g., stars, star clusters, and background galaxies) can be identified and measured. Traditional approaches (isophotal or parametric fitting) are semiautomated and can be challenging for large datasets. We build a convolutional denoising autoencoder (DAE) for galaxy model subtraction: images are compressed to a latent representation and reconstructed to yield the smooth galaxy, suppressing other objects. The DAE is trained on GALFIT-generated model galaxies injected into real sky backgrounds and tested on real images from the Next Generation Virgo Cluster Survey. To quantify performance, we conduct an injection-recovery experiment on residual images by adding mock globular clusters (GCs) with known fluxes and positions. Our tests confirm a higher recovery rate of mock GCs near galaxy centers for complex morphologies, while matching ellipse fitting for smooth ellipticals. Overall, the DAE achieves subtraction equivalent to isophotal ellipse fitting for regular ellipticals and superior results for galaxies with high ellipticities or spiral features. Photometry of small-scale sources on DAE residuals is consistent with that on ellipse-subtracted residuals. Once trained, the DAE processes an image cutout in ≲0.1 s, enabling fast, fully automatic analysis of large datasets. We make our code available for download and use.